Collaborative Geospatial Data as Applied to Disaster Relief: Haiti 2010 - Clark, A. J.; Holliday, Patton; Chau, Robyn; Eisenberg, Harris; Chau, Melinda (Security Technology, Disaster Recovery and Business Continuity, 2010)
The aftermath of Haiti’s January 12 earthquake typified disaster relief in that efficiency and situational awareness were reduced by the chaotic, uncoordinated influx of relief and aid. The lack of an environment in which information could be shared was a major component of this chaos. The application of geographic information (GIS) technology was a significant contribution to the relief efforts due to the centrality of location to issues of danger, resources, safety, communications, and so on, and due to the universal understanding of information rendered geospatially using 3-D globes. Concerned that existing solutions were restricting, U.S. Southern Command (SOUTHCOM) engaged Thermopylae to build a user-friendly GIS tool to reach a wide user base, fuse data from disparate sources, and immerse users in relevant content. The resulting SOUTHCOM 3D User-Defined Operational Picture (UDOP) united over 2,000 users to create, add, edit, update, and share data aggregated through GIS tools, existing databases, mobile applications and other resources, geospatially. The UDOP was built on the enterprise geospatial framework, iSpatialTM, which interacts with the Google Earth Plug-inTM browser application programming interface and provided SOUTHCOM’s Joint Intelligence and Operations Center with interactive applications and an open platform for the integration of dynamic data for timely and publicly-accessible solutions. The application of the UDOP to relief efforts in Haiti optimized the gathering and management of data from government, military, non-government agency, and first responder resources, which consequently improved relief efforts simply by inviting a large user community to share data on an intuitive common platform. The experience in and lessons learned from Haiti promise great strides into the future of the geospatial technology.